Earthquake Brain: Altered Recognition and Misclassification of Facial Expressions Are Related to Trauma Exposure but Not Posttraumatic Stress Disorder - Bell, Caroline J.; Colhoun, Helen C.; Frampton, Chris M.; Douglas, Katie M.; McIntosh, Virginia V. W.; Carter, Frances A.; Jordan, Jennifer; Carter, Janet D.; Smith, Rebekah A.; Marie, Leila M. A.; Loughlin, Alex; Porter, Richard J. (Frontiers in Psychiatry, 2017)
Objectives The study investigated Facial Expression Recognition (FER) in Posttraumatic Stress Disorder (PTSD) caused by exposure to earthquakes, and in particular whether people with this condition showed a bias towards interpreting facial expressions as threat related emotions (i.e., as anger, fear or disgust). The study included a trauma-exposed control group who had been similarly exposed to the earthquakes but had not developed PTSD. We hypothesised that individuals with PTSD would have increased sensitivity to threat related facial emotions compared with the trauma-exposed control group. This would be shown by increased accuracy in recognition of threat related emotions and the misinterpretation of neutral expressions to these emotions (i.e. misidentifying them as anger, fear or disgust). The availability of a group of healthy controls from a previous study who had been tested on a similar task prior to the earthquakes allowed a further non-exposed comparison. Method Twenty-eight individuals with PTSD (71% female, mean age 42.8 years), and 89 earthquake-exposed controls (66% female, mean age 50.1 years) completed an FER task which featured six basic emotions. Further comparisons were made with 50 non-exposed controls (64% female, mean age 38.5 years) who had been tested before the earthquakes. Results There was no difference in sensitivity to threat related facial expressions (as measured by accuracy in recognition of threat related facial expressions and the misinterpretation of neutral expressions as threatening) in individuals with PTSD compared with similarly earthquake-exposed controls. Supplementary comparison with an historical, non-exposed control group showed that both earthquake-exposed groups had increased accuracy for the identification of all facial emotions and showed a bias in the misclassification of neutral facial expressions to the threat-related emotions of anger and disgust. Conclusion These findings suggest that it is exposure to earthquakes and repeated aftershocks, rather than the presence of PTSD that affects facial expression recognition accuracy and misinterpretation. The importance of these biases in both PTSD and trauma-exposed controls needs further exploration, and is an area for future research.